Antithrombotic and antiplatelet activity of an organometallic rhodium(I) complex incorporating a substituted thieno‐[2, 3‐d]‐pyrimidine ligand: Synthesis, structural characterization, and molecular docking calculations. (15th February 2021) - Kalampalidis, Alexandros; Peppas, Anastasios; Schnakenburg, Gregor; Papakyriakou, Athanasios; Tsoupras, Alexandros; Zabetakis, Ioannis; Philippopoulos, Athanassios I.
Abstract : The antiplatelet and antithrombotic activity of a novel organometallic rhodium(I) complex of the formula [Rh(cod)Cl(tpc )] (1 ) (cod = cis ‐1, 5‐cyclooctadiene; tpc = methyl 2‐amino‐4‐(diethylamino)‐thieno‐[2, 3‐ d ]‐pyrimidine‐6‐carboxylate) was investigated. Complex 1 was easily synthesized by a one‐pot, high‐yield reaction and was fully characterized by standard spectroscopic techniques including FT‐IR, UV–Vis, and NMR spectroscopy and by elemental analysis. The molecular structures of tpc and 1 were determined by single‐crystal X‐ray crystallography. Complex 1 displayed a slightly distorted square planar geometry and is the first crystallographically characterized example of a coordination compound bearing the ligand precursor tpc . Biological studies demonstrate that 1 displays strong antiplatelet and antithrombotic properties in vitro, by inhibiting both the aggregation of human and washed rabbit platelets induced by the potent inflammatory and thrombotic mediator, platelet‐activating factor (PAF) in the micromolar range. This is an approach of continuous interest in the field. Molecular docking calculations suggest that 1 can fit at the ligand‐binding site of the PAF receptor (PAFR) and thus block PAF thrombotic activities, through an antagonistic effect on the PAF/PAFR‐related pathway, which is in accord with the experimental findings. Complex 1 constitutes an interesting example of a metal‐based PAF inhibitor with promising antiplatelet, antithrombotic, and anti‐inflammatory activity, because PAF is the most potent inflammatory lipid mediator. This is also supported by the fact that 1 is an inhibitor of other inflammatory and thrombotic mediators like thrombin, along with well‐established platelet agonists like ADP and collagen. Abstract : The square planar organometallic complex [Rh(cod)Cl(tpc )] (1 ) (cod = cis ‐1, 5‐cyclooctadiene; tpc = methyl 2‐amino‐4‐(diethylamino)‐thieno‐[2, 3‐ d ]‐pyrimidine‐6‐carboxylate) displays strong antiplatelet and antithrombotic activity as this is expressed by its potency to inhibit the PAF‐induced aggregation of human platelets and washed rabbit platelets in the micromolar range. Molecular docking analysis suggests that 1 can be accommodated within the ligand‐binding site of PAF receptor interacting with key agonist‐binding residues.